DAKWAH BERNUANSA KETEGARAN HUKUM AGAMA: (Studi Atas Konstruksi Dakwah Habib Mustafa Al-Djufri) - Imam Safii (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2020)
The presence of this paper is motivated by the presence of a number of preachers who prioritize the value of entertainment in their da'wah rather than the values of preaching delivered to a mad'u. Many of us say that this preacher is comfortable speaking because he is able to keep the madam entertained (laughs). This article examines the missionary work of a kiai in his community, Habib Mustafa Al-Djufri, a unique kiai figure who is different from other kiai in general. There is a special attraction in all aspects of life for the Situbondo community. The findings obtained in this paper are: Da'wah social construction of Habib Mustafa in the process of externalization is a process of self-adaptation to the socio-cultural world, social construction of the objectivation process is the creation of a propaganda product by making the experience of preaching so that the creation of a new propaganda product that forces for the apply in real life. The next thing is social construction in the process of internalization is a moment of self-socialization on propaganda products that are applied to social reality, namely the formation of Habib Mustafa's social constructions which consist of three ways of socialization: a) by preaching bi al oral b) by preaching bi al qolam and c ) with propaganda bi al p. In applying the three moments above and then becoming the social reality of da'wah which is the main basis here there are all forms of values in religion.